THE KNOWLEDGE OF THE TODDLER’S MOTHER AND ITS ASSOCIATION 1,2,3 WITH IODINE INTAKE IN DARUL IMARAH, ACEH BESAR DISTRICT - Intan Sari; Nurbaiti; Asriah (Journal of Midwifery and Community Health (JMCH), 2022)
Introduction: The disorders due to iodine deficiency (GAKY) in Indonesia are one of the major public health problems given its enormous impact on the survival and quality of human resources. In addition, Iodine deficiency that occurs in infants will result in impaired nerve, mental, and physical development called cretinism and also enlargement of the thyroid and hypothyroidism. All of these disorders result in low learning achievement in school-age children, low work productivity for adults, and the emergence of various socio-economic problems in the community that can hinder economic growth.  This study aim to analyzed the knowledge of the toddler’s mother regarding the iodine intake in the sub-district of Darul Imarah , Aceh Besar in 2019 Method: This study was a descriptive-analytical survey with a cross sectional in the subdistrict of Darul Imarah, Aceh Besar from 15-25 March 2019. The population in this study were all mothers who had toddlers aged 24-59 months in the subdistrict of Darul Imarah. The sample in this study were mothers of toddlers in the Darul Imarah region, the total sample was 95 people who met the inclusion and exclusion criteria. Two-stage sampling technique was used, which consisted of purposive sampling and stratified random sampling. The instrument in this study was a questionnaire. Result: There were 52 respondents (54,7%) of mothers who have high knowledge and 70 respondents (73,7%) of mothers who do not have iodine intake. In the bivariate analysis shows that there were 43 respondents (82,7%) of mothers who had high knowledge but did not have iodine intake, and 27 respondents (62,8%) of mothers who had low knowledge and not having iodine intake. There was an association between the mother’s knowledge and iodine intake Conclusion: There was an association between the mother’s knowledge and iodine intake of their child in the Sub-district of Darul Imarah.